The nexus of employers demands and employability skills in Oyo State Nigeria: implications on japa syndrome (2023)
This study examines the required employability skills and how important is such employability skills to an employer of labours in Oyo State, Nigeria. Two research questions were answered. The study adopted the sequential mixed methods research design. The multi-stage sampling procedure was used in this study. The economic sectors were stratified into seven sectors in Ibadan Metropolis. 20 employers of labour were selected from each sector using a convenience sampling technique. A total of 140 employers were used for the study. 10 human resources managers were purposively selected as Key informants for interview sections using an interview guide. Two validated instruments of reliability of 0.75 and 0.78 respectively were used to collect the data. Quantitative data were analysed using the descriptive statistic of frequency count, percentage, mean, and standard deviation while qualitative data were content analysed and thematically interpreted. The results obtained revealed that employers strongly agreed that communication, Information Communication and Technology, Problem-Solving, Analytical, Personality, Adaptability, Team Work, and Leadership skills were essential for graduates to have in order to be employable. It can therefore be inferred that the possession of a certificate is only to attest to the fact that someone has been trained in formal settings. Job seekers should display good communication skills, organisation skill, creativity, teamwork, planning, and so on, which are in high demand by the employers of labour. Among others, some recommendations were made that the management of various educational institutions should put more emphasis on experiential learning to gain practical experience through service learning, internships, volunteer work, teaching practice, or part-time jobs to expose learners to employability skills in terms of, organisation skill, creativity, teamwork and, planning. Also, counselling section should be put in place to re-orientate the graduate on Japa syndrome among others.